Smallholder participation in the commercialisation of vegetables: Evidence from Kenyan panel data - Beatrice W. Muriithi; Julia Anna Matz (University of Bonn, Center for Development Research (ZEF), 2014)
This paper describes the participation of smallholders in commercial horticultural farming in Kenya and identifies constraints and critical factors that influence their decision to participate in this industry by selling their produce. The study employs panel survey data on smallholder producers of both international (export) and domestic market vegetables and controls for unobserved heterogeneity across farmers. We find that participation of smallholders in both the domestic and export vegetable markets declined and that this trend is associated with weather risks, high costs of inputs and unskilled labour, and erratic vegetable prices, especially in the international market. Different factors are at play in determining a households market choice for the commercialisation of vegetables: credit is important only when vegetables are (also) exported, livestock ownership is negatively related to production for the domestic market, and distance to the nearest market town positively related to all pathways of commercialisation, for example.
Keywords: O10; Q12; Q13; Q17; 330; horticulture; commercialisation; smallholders; Kenya